RT-PCR for detection of bovine parainfluenza virus type 3 (bPIV-3) - Vaucher, Rodrigo de Almeida; Simonetti, Amauri Braga; Roehe, Paulo Michel (Acta Scientiae Veterinariae, 2018)
The RT-PCR technique has been frequentely used for detection of the human parainfluenza virus type 3 (hPIV-3) but the literature is scarce in relation to the bovine parainfluenza virus type 3 (bPIV-3). The aim of this study was to describe a reverse transcriptase polymerase chain reaction (RT-PCR) for detection of bovine parainfluenza virus type 3 (bPIV-3) using degenerate oligonucleotides targeting a conserved region of hemagglutinin-neuraminidase (HN) gene. Reference strain SF-4 and three different brazilian bPIV-3 isolates, besides five viral strains from different sources, were included in this study. Viruses were cultured in MDBK cells under standard conditions. Hemagglutination (HA) test was used for viral titration and a direct immunofluorescence test (DFAT) for isolate screening. In RT-PCR all bPIV-3 isolates showed amplification of an expected 1009 bp fragment of HN gene, as oposed to non PIV-3 viral samples where no amplification was detected. Using SF-4 as positive control, sensitivity of 95 pg cDNA wasachieved. In spite of the low number of bPIV-3 isolates tested, the results obtained in this study point out the potential use of this technique for detection of bPIV-3 in bovine clinical specimens.